2004
DOI: 10.4049/jimmunol.173.7.4286
|View full text |Cite
|
Sign up to set email alerts
|

Divergent Trophoblast Responses to Bacterial Products Mediated by TLRs

Abstract: Intrauterine infections have been associated with pregnancy complications that are also linked with increased trophoblast apoptosis. TLRs are key components of the innate immune system which recognize conserved sequences on the surface of pathogens and trigger effector cell functions. We hypothesize that intrauterine infections may cause the excessive trophoblast cell apoptosis observed in abnormal pregnancies and that TLR may provide a mechanism of pathogenesis. In this study we describe the expression and fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
293
2
10

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 254 publications
(321 citation statements)
references
References 81 publications
16
293
2
10
Order By: Relevance
“…This response is amplified by LPS-induced uterine NK cell synthesis of IFN-␥ (47). Cytokine responses in decidual leukocytes are augmented by increased production of a range of inflammatory cytokines, including TNF-␣, IL-1, IL-6, and IL-12 in choriodecidual membranes (49) and placental trophoblast cells (50).…”
Section: Discussionmentioning
confidence: 99%
“…This response is amplified by LPS-induced uterine NK cell synthesis of IFN-␥ (47). Cytokine responses in decidual leukocytes are augmented by increased production of a range of inflammatory cytokines, including TNF-␣, IL-1, IL-6, and IL-12 in choriodecidual membranes (49) and placental trophoblast cells (50).…”
Section: Discussionmentioning
confidence: 99%
“…Ten different human TLRs, each responding to a specific set of ligands, have been identified [4]. TLR expression and activation in primary trophoblasts [5][6][7][8][9][10] may contribute substantially to development of inflammatory pregnancy complications such as preeclampsia [11][12][13]. In Tangerås/Stødle et al [7] we demonstrated a broad functional TLR profile in primary first trimester trophoblasts, while the trophoblast cell line BeWo showed no TLR mediated cytokine response.…”
Section: Introductionmentioning
confidence: 95%
“…TLR2 and TLR4 protein expression in human placenta is strongest on the trophoblasts that cover the peripheral chorionic villi and which constitute the immediate barrier between mother and fetus [35]. Trophoblasts can produce cytokines following TLR4 ligation, but undergo apoptosis following TLR2 ligation [1].…”
Section: Pathogen Recognitionmentioning
confidence: 99%
“…Chlamydial hsp60 can activate cells through ligation of TLR4 [11], whereas C. trachomatis LPS is recognised by TLR2 [23]. Activation via TLR2 but not TLR4 in human trophoblasts can lead to apoptosis in vitro [1]. If this occurs during placental infection with C. abortus, the resulting damage to the placenta could compromise the pregnancy.…”
Section: Route Of Infectionmentioning
confidence: 99%